Guidance for the Treatment and Management of COVID‐19 Among People with Intellectual Disabilities. Issue 3 (10th June 2020) - Alexander, Regi; Ravi, Ambiga; Barclay, Helene; Sawhney, Indermeet; Chester, Verity; Malcolm, Vicki; Brolly, Kate; Mukherji, Kamalika; Zia, Asif; Tharian, Reena; Howell, Andreana; Lane, Tadhgh; et al.
Abstract: The current COVID‐19 pandemic is a pressing world crisis and people with intellectual disabilities (IDs) are vulnerable due to disparity in healthcare provision and physical and mental health multimorbidity. While most people will develop mild symptoms upon contracting severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2), some will develop serious complications. The aim of this study is to present guidelines for the care and treatment of people with IDs during the COVID‐19 pandemic for both community teams providing care to people with IDs and inpatient psychiatric settings. The guidelines cover specific issues associated with hospital passports, individual COVID‐19 care plans, the important role of families and carers, capacity to make decisions, issues associated with social distancing, ceiling of care/treatment escalation plans, mental health and challenging behavior, and caring for someone suspected of contracting or who has contracted SARS‐CoV‐2 within community or inpatient psychiatric settings. We have proposed that the included conditions recommended by Public Health England to categorize someone as high risk of severe illness due to COVID‐19 should also include mental health and challenging behavior. There are specific issues associated with providing care to people with IDs and appropriate action must be taken by care providers to ensure that disparity of healthcare is addressed during the COVID‐19 pandemic. We recognize that our guidance is focused upon healthcare delivery in England and invite others to augment our guidance for use in other jurisdictions.